Efficacy of neuromuscular training for enhancing postural stability in young athletes: a systematic review and meta-analysis - Zhou, J.; Liu, S.; Sun, H.; Zheng, X. (Frontiers in Physiology, 2026)
Background: Postural stability is vital for athletic performance and injury prevention in young athletes. While neuromuscular training (NMT) is common, its specific effects on different stability components and optimal training parameters remain unclear. This systematic review and meta-analysis evaluated the efficacy of NMT on dynamic and static postural stability in young athletes.